Advances in single‐cell sequencing and its application to musculoskeletal system research. Issue 1 (9th December 2021) - Zhang, Yongxiang; Wang, Jingkai; Yu, Chao; Xia, Kaishun; Yang, Biao; Zhang, Yuang; Ying, Liwei; Wang, Chenggui; Huang, Xianpeng; Chen, Qixin; Shen, Li; Li, Fangcai; et al.
Abstract: In recent years, single‐cell sequencing (SCS) technologies have continued to advance with improved operating procedures and reduced cost, leading to increasing practical adoption among researchers. These emerging technologies have superior abilities to analyse cell heterogeneity at a single‐cell level, which have elevated multi‐omics research to a higher level. In some fields of research, application of SCS has enabled many valuable discoveries, and musculoskeletal system offers typical examples. This article reviews some major scientific issues and recent advances in musculoskeletal system. In addition, combined with SCS technologies, the research of cell or tissue heterogeneity in limb development and various musculoskeletal system clinical diseases also provides new possibilities for treatment strategies. Finally, this article discusses the challenges and future development potential of SCS and recommends the direction of future applications of SCS to musculoskeletal medicine. Abstract : Single cell sequencing (SCS) technologies have superior abilities to analyze cell heterogeneity at a single‐cell level, which have elevated omics research to a higher level. Meanwhile, the applications of SCS have enabled many valuable discoveries, and musculoskeletal system offers typical examples. Single cell sequencing of bone, muscle, articulation and cartilage produces a great deal of valuable data. Through integration analysis and visualization, the musculoskeletal system heterogeneity is revealed, which provide new clues for regeneration and disease treatment.